Italy's Superbonus 110%: Messing up with demand stimulus and the need to reinvent fiscal policy - Lorenzo Codogno (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2024)
Since the Global Financial Crisis in 2008-2009, there has been flourishing literature on the role of fiscal policy in stimulating demand when the economy is in a deep recession. Past studies suggest the stimulus may make sense if it is temporary, targeted, and withdrawn quickly. However, since the pandemic, there has been a case for going big, when necessary, to prop up expectation, confidence and demand. This was exemplified by Italy's Superbonus 110%, a generous subsidy scheme to allow the energy-efficient renovation of residential buildings, which emerged as a significant policy response to the economic challenges posed by the pandemic. I argue that the Superbonus, while having a respectable economic aim, ended up impinging on the same sectors supported by the EU-funded investment plan, resulting in significant capacity constraints and misallocation of resources. Its excessive generosity brought a massive deterioration in public finances, while its returns in terms of economic growth were short of expectations. I conclude by drawing some policy lessons from Italy's experience, on what should be preserved and avoided, and on a possible reinvented role for fiscal policy in deep economic crisis.
Keywords: E61; H60; H12; 330; Policy Designs and Consistency; National Budget; Deficit and Debt; Crisis management